PENERAPAN PENDEKATAN SETS PADA PEMBELAJARAN FISIKA UNTUK MENINGKATKAN PENGAKUAN TERHADAP KEAGUNGAN SANG PENCIPTA (UPEJ Unnes Physics Education Journal, 2013)
The research was distributed by learning from school less providing education that links science impact of technology on the environment. To overcome these problems, applied approach to learning SETS. But in the thought of the author of the application of education SETS will have more impact that more real to students if it is given a religious element. It is also based on the results of the interviews of students in MAN Purwodadi, apparently the many students consider that science does not have to do with religion (Al Quran). They never study the Quran with the science they are learning. This aim is a research described the application of the approach to the study of physics SETS that are associated with the elements of religion (Qur'an) to enhance the recognition of the greatness of the creator. This research is research that is implemented in the class action is three cycles. The location of the research was on the MAN Purwodadi. The subject of this research is the grade XI IPA 2. Research data in the form of affective learning outcomes obtained from the now and the results of the cognitive learning of evaluation questions. To find out of attitude increases the recognition of God's greatness and overall student learning outcomes used test gains. The results of the analysis of the data showed science learning with approaches SETS on the material law of gravity Newton with associated to Al Quran can increase recognition of the positive attitude of greatness about creator lodly and student learning outcomes.